2015
DOI: 10.1017/thg.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

Food Preference Patterns in a UK Twin Cohort

Abstract: Food liking-disliking patterns may strongly influence food choices and health. Here we assess: (1) whether food preference patterns are genetic/environmentally driven; and (2) the relationship between metabolomics profiles and food preference patterns in a large population of twins. 2,107 individuals from TwinsUK completed an online food and lifestyle preference questionnaire. Principle components analysis was undertaken to identify patterns of food liking-disliking. Heritability estimates for each liking patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 40 publications
(69 reference statements)
7
70
3
Order By: Relevance
“…Survey-reported preferences for foods/beverages can serve as proxy of usual intake as supported by its correlation with biomarkers of nutritional status [Pallister et al, 2015;Sharafi et al, 2015Sharafi et al, , 2016. Assessing preference is cognitively easier than recalling behavior [Johnson, 1983] required of dietary assessment/screening tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey-reported preferences for foods/beverages can serve as proxy of usual intake as supported by its correlation with biomarkers of nutritional status [Pallister et al, 2015;Sharafi et al, 2015Sharafi et al, , 2016. Assessing preference is cognitively easier than recalling behavior [Johnson, 1983] required of dietary assessment/screening tools.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, asking about food/beverage preference is cognitively simpler, quicker and often less biased. Reported food preference correlates with reported intake [Lanfer et al, 2012;Sharafi et al, 2015;Tuorila et al, 2008] and biomarkers of dietary intake and/or adiposity in children and adults [Pallister et al, 2015;Sharafi et al, 2016]. Elevated preference for sweet foods is observed among children who have greater adiposity [Lanfer et al, 2012] and caries [Maciel et al, 2001].…”
Section: Introductionmentioning
confidence: 94%
“…Genetic variation in sensitivity to bitter taste of thioureas and related compounds (PROP taster status) has been associated with children lower acceptance of bitter-tasting vegetables (Bell & Tepper, 2006). Studies on twin population showed a moderate heritability of fruit and vegetable preference (Pallister et al, 2015) and genes regulating sour taste perception has been hypothesized to be relevant in the acceptability of naturally sour products such as fruits, berries and vegetables (Törnwall, Silventoinen, Hiekkalinna, Perola, Tuorila and Kaprio, 2014).…”
mentioning
confidence: 99%
“…Studies from TwinsUK have successfully identified potential biomarkers of alcohol intake (28) including lysophosphatidylcholines, diethyl ether lipids, diaclylphosphatidycholines and sphingolipids, as well as biomarkers of self-reported dietary patterns (22) , food preference patterns (9) and self-reported food intakes (29,30) . Taking advantage of the twin nature of the TwinsUK data, we first looked for association in the larger twin population excluding MZ twins discordant for a nutritional intake.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Specific foods intakes, including garlic (46 %), fruit and vegetables (49 %), and coffee (41 %) are also highly heritable in adults (8) . A recent study from our group identified four major food-liking patterns (fruit and vegetables, distinctive tastes, sweet and high carbohydrate, and meat) accounting for 26 % of the total variance with heritability estimates ranging from 36 to 58 % indicating genetic factors influence food liking-disliking (9) . Besides estimating heritability of dietary assessment, using MZ twins discordant for dietary factor/nutrition status provides a naturally unique case-controlled experiment of assessing the links between diet and human biology.…”
mentioning
confidence: 99%